Fenomena â€œQuick Countâ€ Mewarnai Pemilu 2004 - Budi Setiawan (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
The role of applied statistics in the process of General Election (Pemilu) 2004 has been a social phenomenon. The pros and contras to the result of vote counting using the â€œQuick Countâ€ method are the evident that some people are still in doubt of the accuracy of the sampling process.Â  In fact, the proper application of sampling method and the empirical facts can assure the accuracy of conclusion and decision making. The benefits of the method are the faster process of the information resulted, and the less opportunity of result modification and manipulation.Â  More important, the government efforts to establish â€œGood Governanceâ€) can be realized as demanded by the society. Â